Evaluation of the sexual health in people living with hemophilia. Issue 6 (19th September 2021) - Germini, Federico; Chai‐Adisaksopha, Chatree; Pete, Drashti; Curtis, Randall; Frick, Neil; Nichol, Michael B.; Noone, Declan; O'Mahony, Brian; Page, David; Stonebraker, Jeffrey S.; Thabane, Lehana; Crowther, Mark A; et al.
Abstract: Background: Knowledge about sexual health, difficulty with sexual activity and intimacy (sexual difficulty), in people with hemophilia is little understood. Objectives: The objectives were to determine the prevalence of sexual difficulty in people living with hemophilia (PWH) compared to people with no bleeding disorders (PWNoBD), and to determine factors associated with it. Methods: This was an analysis of the PROBE study. We recruited individuals who had hemophilia A or B (PWH) and PWNoBD who were 18 years old or older. We calculated proportions of participants with sexual difficulty and odds ratios (ORs) adjusted for sex and age with 95% confidence intervals. Results: There were 2007 PWH and 1972 PWNoBD. Mean (standard deviation) age was 41 (15) years in PWH and 42 (13) years in PWNoBD. Sexual difficulty was reported in 302 (15.1%) PWH and 79 (4.0%) PWNoBD. The odds of sexual difficulty were significantly higher in PWH (OR 3.82, 95% CI 2.85, 5.11). Among PWH, older age, experiencing acute or chronic pain in the past 12 months, bleeds within the past two weeks, ≥3 spontaneous joint bleeds (past six months), limitation of range of motion of any joints, and any life‐ or limb‐threatening bleeds in the past 12 months were associated with sexual difficulty. Conclusions: Sexual difficulty is more prevalent in people living with hemophilia and associated with markers of disease severity. Sexual health issues should be incorporated in comprehensive hemophilia care, future research, and hemophilia related health policy.